The Estimation Modeling of Abutment Volume with Variations of Bridge Span, Abutment Height, and Seismic Zone - Dicky Rahadian Mahendra; Andreas Triwiyono (Journal of the Civil Engineering Forum, 2021)
The initial cost of a bridge project determined using an estimation model depends on the dimensions, types, and materials but only a few studies have included bridge location as a determinant variable. The inclusion of the location is, however, important due to the different seismic accelerations and seismic load analysis attached to it. Therefore, this study aimed to create a model to calculate the quantity of materials needed for the construction of abutment in different locations with a PCI-Girder superstructure. Moreover, the data used for the quantity estimation model was derived from the abutment design results and those associated with concrete and reinforcing steel quantities were based on the variations of the bridge span at 20 m, 25 m, 30 m, 35 m, and 40 m, abutment height at 4 m, 6 m, and 8 m, and seismic zone 1, 2, 3, and 4. Meanwhile, the volume estimation models were obtained through multiple linear regression analysis. The results showed a very strong correlation between the span of the bridge and the height of abutment with the dependent variables while the seismic zone was observed to have a strong correlation with the dependent variables but was unable to meet the linear regression assumptions. Therefore, the statistical analysis was conducted separately for each seismic zone and the data for abutment height was transformed from H into H2. This study developed 8 models with R2 values ranging between 0.983 – 0.997 and this means they were adequately designed to estimate abutment volumes with a PCI-Girder superstructure.